2015
DOI: 10.1007/s40808-015-0003-8
|View full text |Cite
|
Sign up to set email alerts
|

Modelling storm responses on a high-energy coastline with XBeach

Abstract: The XBeach model has been used to simulate the morphological impacts of storms on sandy and gravel beaches. Taking as a case study Rossbeigh Spit located on the high-energy coast of western Ireland, the study reported here tests the capacity of XBeach to reproduce barrier breaching during a storm in December 2008. It demonstrates that predictions of the breaching event agree reasonably well with observations. However, the main focus of the paper is to establish using the model results, sitespecific critical wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 16 publications
1
26
0
1
Order By: Relevance
“…Predictions of the breaching event morphodynamics by XBeach demonstrated reasonably agreement with the observations (Williams et al, 2015). However, as is frequently the case in most coastal studies of this nature, the data describing the hydrodynamics, waves and the bathymetry and topography were incomplete and recourse to hindcast data and varied data sources to establish the pre-and post-storm bathymetry was required.…”
Section: Rossbeigh Spit Irelandsupporting
confidence: 63%
“…Predictions of the breaching event morphodynamics by XBeach demonstrated reasonably agreement with the observations (Williams et al, 2015). However, as is frequently the case in most coastal studies of this nature, the data describing the hydrodynamics, waves and the bathymetry and topography were incomplete and recourse to hindcast data and varied data sources to establish the pre-and post-storm bathymetry was required.…”
Section: Rossbeigh Spit Irelandsupporting
confidence: 63%
“…As a result, brackish water aquaculture is being popular over rice cultivation for high returns. It has been reported that the rapid expansion of coastal aquaculture in India is responsible for landscape transformation, such as mangrove deforestation and loss of agricultural land (Vadlapudi 2003;Hein 2000;Hossain et al 2002;Rajitha et al 2007). Recent studies revealed that the landuse/landcover along the coastal border of West Bengal is being changing rapidly mainly due to the mushrooming of aquaculture firms (Mitra and Santra 2011;Samanta and Hazra 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the Inch Spit appears to be relatively stable today, Rossbehy was breached by a storm surge in 2008. The loss of dune volume reached a maximum of 530,000 m 3 /yr in 2008 and culminated in the 13-14 December 2008 breach which left a small northern island at around 500 m from the southern dune systems at high water (Williams et al, 2015). Henceforth, the erosion rates continue at rates of 30-50 m/yr along its core-length and at circa 25 m/yr on the seaward shore face, with the breach doubling in size to 1400 m width from 2012-2014.…”
Section: Low Sustainability Practicesmentioning
confidence: 99%
“…Breaching events will likely become more frequent in response to rising sea levels due wave action at higher elevations across beach and dune profiles (Williams et al, 2015). Under future SLR associated to climate warming (about 0.8 m SLR by 2100 for the RCP 8.5, see Section 3) this structure may disintegrate, with significant impacts on Inch and the morpho-hydrodynamics of neighbouring coastal systems, though the barrier may reform in part or possibly move further east on land (Church et al, 2013;O'Shea and Murphy, 2013;Devoy, 2015a).…”
Section: Low Sustainability Practicesmentioning
confidence: 99%
See 1 more Smart Citation